CONTENT-BASED INSTRUCTION: A COMMUNICATIVE APPROACH FOR THE EFL CLASSROOM - Hull, Todd (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Content-Based Instruction (CBI)1 is a justifiably popular method in the ESL/EFL classroom because it combines the improvement of competency in a foreign language with the attainment of knowledge in various subjects that occur in academic curricula across the spectrum of higher education. CBI has two main focuses. One concentrates on imparting knowledge of a particular subject matter with a secondary goal of improving language ability. The other aims primarily at the improvement of communicative competence in the target language. The focus of this paper is on this second aspect. Here learners are first given content that provides a basic overview of a particular subject or current issue. They are then tasked with performing various classroom activities that promote proficiency in the target language through engaging with the subject matter. The great advantage of this format is that, in addition to improving students’ general knowledge about the world, practice in all four major skills is given in the course of a single lesson. Reading is enhanced when students research the topic to be addressed in class. Writing is practiced when students do timed essays, which not only improves their writing but also simulates writing done for language assessment tests such as the TOEFL and IELTS. Opportunities to improve listening and speaking come when students engage classmates in discussions about the topics addressed in class. This paper gives practical examples of how to implement such lessons in the EFL classroom as CBI continues to become more relevant now and into the future.